Association between leukoreduced red blood cell transfusions and hospital‐acquired infections in critically ill children: A secondary analysis of the TRIPICU study. Issue 4 (24th November 2021) - Flatman, Leah K.; Fergusson, Dean A.; Lacroix, Jacques; Ducruet, Thierry; Papenburg, Jesse; Fontela, Patricia S.
Abstract: Background and Objectives: Hospital‐acquired infections (HAIs) are an important problem in critically ill children. Studies show associations between the transfusion of non‐leukoreduced red blood cell units (RBC) and increased HAI incidence rates (IRs). We hypothesize that transfusing pre‐storage leukoreduced RBC is also associated with increased HAI IR. We aim to evaluate the associations between (1) a leukoreduced RBC restrictive transfusion strategy and HAI IR, (2) leukoreduced RBC transfusions and HAI IR, and (3) the number or volume of leukoreduced RBC transfusions and HAI IR in critically ill children. Materials and Methods: This post hoc secondary analysis of the "Transfusion Requirement in Paediatric Intensive Care Units" (TRIPICU) randomized controlled trial (637 patients) used quasi‐Poisson multivariable regression models to estimate HAI incidence rate ratios (IRRs) and 95% confidence intervals (CI). Results: A restrictive transfusion strategy yielded an IRR of 0.88 (95% CI 0.67, 1.16). The association between transfusing leukoreduced RBCs (IRR 1.25; 95% CI 0.73, 2.13) and HAI IR was not statistically significant. However, we observed significant associations between patients who received >20 cc/kg volume of leukoreduced RBC transfusions (IRR 2.14; 95% CI 1.15, 3.99) and ≥3 leukoreduced RBC transfusions (IRR 2.40; 95% CI 1.15, 4.99) and HAI IR. Conclusion: Exposing critically ill children to >20 cc/kg or ≥3 leukoreduced RBC transfusions were associated with higher HAI IR, suggesting dose–response patterns.